2011
DOI: 10.1016/j.jss.2011.06.010
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Complement Control on Endothelial Barrier Reduces Renal Post-Ischemia Dysfunction

Abstract: Background Excessive complement activation is an integral part of ischemia and reperfusion (IR) injury (IRI) of organs. In kidney transplantation the pathological consequence of IRI and complement activation can lead to delayed graft function which in turn is associated with acute rejection. Previous strategies to reduce complement induced IRI required systemic administration of agents, which can lead to increased susceptibility to infections/immune diseases. The objective of this study was to determine whethe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 52 publications
(46 reference statements)
0
10
0
Order By: Relevance
“…Delayed graft function is characterised by tubular dysfunction, interstitial inflammation, and altered microcirculation (Moore et al 2008 ; Ponticelli 2014 ). Several studies have shown that complement may be involved in the pathogenesis of DGF (Castellano et al 2016 ; Damman et al 2015 ; Pushpakumar et al 2011 ; Yu et al 2016 ). Yu et al ( 2016 ) have shown that blocking the terminal complement pathway prevented reperfusion injury and increased renal graft survival.…”
Section: Discussionmentioning
confidence: 99%
“…Delayed graft function is characterised by tubular dysfunction, interstitial inflammation, and altered microcirculation (Moore et al 2008 ; Ponticelli 2014 ). Several studies have shown that complement may be involved in the pathogenesis of DGF (Castellano et al 2016 ; Damman et al 2015 ; Pushpakumar et al 2011 ; Yu et al 2016 ). Yu et al ( 2016 ) have shown that blocking the terminal complement pathway prevented reperfusion injury and increased renal graft survival.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that IRI activates many signaling pathways and upregulates many genes that eventually lead to complement cascade activation and therefore cell apoptosis and death [46]. In one study, mouse kidneys were flushed with and preserved in a solution containing a cocktail small interference RNA (siRNA) targeting complement 3, RelB, and Fas expression.…”
Section: Machine Perfusion: a Platform For Organ Treatmentmentioning
confidence: 99%
“…Complement C3 expression on the donor also plays an important role in donor injury during ischaemia [8]. Complement inhibition in brain dead donors has been shown to improve graft function [9], and several targeted complement inhibition approaches are now being investigated [10 ▪ ]. …”
Section: Cellular Events Associated With Renal Ischaemic Injurymentioning
confidence: 99%